Responses to the Covid-19: A Political Economic Analysis - Nepal, Ratna Mani (Nepalese Journal of Development and Rural Studies, 2020)
The Covid-19 pandemic posed serious threats to the national and international communities. Worldwide responses to combat its effects seemed weak and controversial. It led individual countries to exercise responses that varied depending upon their tradition, institutions, and leadership. What worked? And what did not? And why is still not comprehended. In this background, this study examines correlation between market economy frameworks such as liberal market economies (LMEs), coordinated market economies (CMEs), state-led market economies (SMEs)and Covid-19 caused deaths. More so, the death cases have been analyzed and interpreted based on published data from worldometer.com as well as national and institutional sources of 23 countries representing three distinct market economy frameworks. The data is juxtaposed with the acts of right-wing populism that determined decision making and institutional mobilization against Covid-19. The approach is dichotomized with a country’s human development index and income inequality index (Gini Index). This study found that a country’s market economy framework has had a correlation with the Covid-19 caused deaths The impact, however, was associated with the acts of right-wing populism within different market economies. The 5 selected countries with LMEs have highest; another 5 selected countries with CMEs have higher and 13 selected countries with SMEs have lowest number of deaths. The findings also proves that rate of human development does not appear to be a valid framework for explaining differing death rates between the countries.